Secesyjne bramy z wytwórni braci Pogorzelskich - przykład krakowskiego przemysłu artystycznego przełomu XIX i XX wieku (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
ART NOUVEAU GATES FROM THE WORKSHOP OF POGORZELSKI BROTHERS - AN EXAMPLE OF CRACOW ARTISTIC CRAFT AT THE TURN OF THE 19TH/20™ C.It is generally believed that industrial products dating from the late 19th and the early 20th century are always the result of mass production, even if they are of significant artistic interest, thus they cannot be considered as works of art. As a result, detailed studies of artistic smithery are virtually non-existent. Fortunately, many mass-made products, such as doors, windows, balusters or balconies are currently attracting the interest of art historians. The article discusses the inspirations which may be traced in forms used in Cracow art-related industries and widens the scope of information on the development of this branch of industry. The author focuses on Art Nouveau metal gates manufactured in the Pogorzelski Brothers’ workshop. A few gates in Cracow townhouses were found to have been made there, so they are no longer anonymous works, thus enriching our knowledge of artistic crafts in Cracow.